The Effect of Loan Interest Rate, Loan Flexibility, And Perceived Risk on the Intention to Use Peer-To-Peer Lending Among MSMEs In Pangkalpinang - Setiawan, Chandra; Wardhani, Rulyanti Susi; Yanto, Yanto (Riset Akuntansi dan Bisnis Indonesia, 2025)
Purpose: This study aims to examine the effects of loan interest rates, loan flexibility, and risk perception on micro, small, and medium-sized enterprises’ (SMEs’) intention to use peer-to-peer (P2P) lending applications in Pangkalpinang. Research methodology: This study uses a quantitative approach with multiple linear regression analysis, employing t- and F-tests to examine the effects of loan interest rates, loan flexibility, and risk perception on micro, small, and medium-sized enterprises’ (MSMEs’) intention to use peer-to-peer (P2P) lending in Pangkalpinang. The sample consists of 103 MSME owners selected through purposive sampling. Results: Loan interest rates, loan flexibility, and risk perception account for 23.1% of the variation in UMKM intention to use P2P lending applications in Pangkalpinang. Barriers include limited understanding, repayment concerns, and low digital literacy, whereas supporting factors include flexible loan options, competitive interest rates, and increasing awareness of digital financial services. Conclusions: Loan interest rates, loan flexibility, and risk perceptions together influence UMKM’s intention to use P2P lending applications. Limitations: This study is confined to one district with a small sample size, limiting its broader applicability. Contribution: This research provides empirical evidence on the impact of the loan interest rate, loan flexibility, and risk perception on UMKM’s intention to use P2P lending in Pangkalpinang, offering practical insights for policymakers and P2P providers to enhance strategies for UMKM adoption of digital financial services